Australian general practice nurse involvement in mental health: A descriptive survey. Issue 4 (August 2022) - Halcomb, Elizabeth; McInnes, Susan; Patterson, Christopher; Moxham, Lorna; Bird, Sonia
ABSTRACT: Background: Early assessment and evidence-based management of depression can significantly improve recovery and enhance well-being. People with depression often present to general practice as their first contact with the health system. Although few general practice nurses have specialist mental health qualifications, to optimise outcomes they must be able to appropriately identify, triage and manage mental health issues such as depression. Aim: To explore the attitudes of general practice nurses about depression and investigate their current roles in mental health care. Design: A descriptive cross-sectional online survey. Methods: An online survey was delivered to nurses working in Australian general practice. An investigator developed survey collected data about participant demographics and their role in mental health within general practice. Attitudes to depression were measured using the Depression Attitudes Questionnaire. Findings: One hundred and four responses were included in the analysis. Findings indicate that participants felt that it was within their role to engage in activities related to mental health care. Participants also disagreed with negative attitudes to depression. Despite this, few participants were currently involved in assessing mental health or developing care plans for those living with mental illness. Few participants had undertaken professional development in mental health topics, although most identified that they felt additional learning would be beneficial. Conclusion: As the first point of contact with the health system, general practice plays an important role in the identification of mental health issues and determining the health services required. In an environment of increasing demand for mental health support, this role cannot be underestimated. With this in mind, the general practice nurse's role in mental health care can have a significant impact on the well-being of the community. Strategies that create opportunities for nurses' engagement in professional development and facilitate the assessment of people's mental health within usual care have the potential to improve the quality of care and health outcomes.